Pola Aktivitas Ibu Rumah Tangga Terhadap Pemanfaatan Ruang Terbuka di Rumah Susun - Mariana, Yosica (ComTech: Computer, Mathematics and Engineering Applications, 2011)
In flat environments, housewives are most found staying throughout the day. They use existing open spaces in housing project to interact with other residents. To find out, discover and analyze the correlation between the pattern of open space utilization and the pattern of activity of housewives at flats, this research was conducted using descriptive analysis method bases on case studies on some flats in urban areas, namely Kebon Kacang Flat (KK), Kemayoran Flat (K), Taman Surya Flat (TS) and Pasar Jumat Flat (PJ). Subjects were housewives (residents of the flats); sampling is taken by stratified random sampling. The survey was conducted by interview to obtain data on activity patterns of the mother. Subsequently, observation was conducted to get an overview of the activity patterns of mothers and use of open space including non-physical and physical data of these open spaces. The implementation was done in three stages: preparation (literature study and data collection by remote sensing), interpretation, field test and re-interpretation (width, location, quality of open spaces and activities, professions of women at these locations), and result presentation.